Alcohol and gastrointestinal cancers. Issue 2 (March 2019) - Vanella, Giuseppe; Archibugi, Livia; Stigliano, Serena; Capurso, Gabriele
Abstract : Purpose of review: Alcohol is a type I carcinogen and the WHO stated that it caused 5% of all deaths in 2016, of which 13% because of cancers. Among digestive tract cancers, this association is clear for esophageal, liver and colorectal cancer, and more debated for gastric and pancreatic cancer. The present review will revise recent evidence on epidemiologic association and mechanisms linking alcohol with the risk of esophageal, gastric, colorectal and pancreatic cancers. Recent findings: Moderate alcohol intake increases the risk of esophageal squamous cell carcinoma and colorectal cancer. Heavy alcohol intake is associated with an increased risk of gastric and pancreatic cancers. These risks also depend on genetic variants and the interaction with smoking is inconsistent. The carcinogenic mechanisms are multiple with a key role of acetaldehyde because of its ability to cause DNA damage, alter telomere length and induce ROS. Data on the role of the gut microbiome as possible mediator of alcohol-induced carcinogenesis are limited. Summary: There is sufficient evidence for the association between alcohol consumption and cancers of the esophagus, stomach, colon–rectum and pancreas. Public health policies to prevent these cancer types should include modification of alcohol intake habits, especially among individuals at increased risk.